The Effect of Decoupling Humidity Control on Aerosol Drug Delivery During HFNC for Infants. - Zhang, Madeline X.; Bem, Reinout A.; Huijgen, Tom; Klein-Blommert, Rozalinde; Bonn, Daniel; van Rijn, Cees J.M. (Respiratory Care, 2025)
Background: Aerosol therapy is commonly used during treatment with high-flow nasal cannula (HFNC) in the ICU. Heated humidification inside the HFNC tubing circuit leads to unwanted condensation, which may greatly limit the efficiency of drug delivery. In this study, we aimed to investigate whether a novel humidification system, which decouples temperature and humidity control, can improve the delivered dose. Methods: In a bench study setup, fluorescein sodium solution was nebulized using a vibrating mesh nebulizer in an infant HFNC circuit to measure the delivered dose, with a conventional versus a decoupled humidifier. The deposition of fluorescein inside each breathing circuit component and a final collection filter at the end of the nasal cannula was collected and quantified with a UV-vis spectrometer. Droplet sizes at different sections of the breathing circuit were measured by laser diffraction. Three air flows, 5, 10, and 15 L/min; and 2 nebulizer positions, (1) at the humidifier and (2) after the inspiratory tube, were tested. Results: The delivered dose decreased with increasing flow for the conventional setup and was higher when the nebulizer was placed after the inspiratory tube. Turning off the conventional humidifier 10 min before and during nebulization did not improve the delivered dose. The decoupled humidifier achieved a significantly higher (P = .002) delivered dose than the conventional setup. The highest delivered dose obtained by the decoupled humidifier was 62.4% when the nebulizer was placed after the humidifier, while the highest dose obtained for the conventional humidifier was 36.3% by placing the nebulizer after the inspiratory tube. Conclusions: In this bench study, we found that the delivered dose for an infant HFNC nebulization setup could be improved significantly by decoupling temperature and humidity control inside the HFNC circuit, as it reduced drug deposition inside the breathing circuit.